Catalysis and tunnelling in the unimolecular decay of Criegee intermediates. Issue 39 (28th September 2018) - Burd, Timothy A. H.; Shan, Xiao; Clary, David C.
Abstract : Semi-classical Transition State theory can be applied to catalysed atmospheric reactions, but reaction mode anharmonicity must be treated carefully. Abstract : The unimolecular decay of Criegee intermediates is the major producer of OH radicals in the atmosphere. Here, Semi-Classical Transition State Theory (SCTST) in full and reduced dimensions is used to determine thermal rate constants for their unimolecular decay, as well as their decay catalysed by a single water molecule. These reactions shed light on the applicability of SCTST for catalysed hydrogen transfer reactions.